Financial fraud and health: the case of Spain - Maria Victoria Zunzunegui; Emmanuelle Belanger; Tarik Benmarhnia; Milena Gobbo; Angel Otero; François Béland; Fernando Zunzunegui; Jose Manuel Ribera-Casado (Elsevier, 2017)
Objective: To examine whether financial fraud is associated with poor health sleeping problems and poor quality of life. Methods: Pilot study (n = 188) conducted in 2015-2016 in Madrid and León (Spain) by recruiting subjects affected by two types of fraud (preferred shares and foreign currency mortgages) using venue-based sampling. Information on the monetary value of each case of fraud; the dates when subjects became aware of being swindled, lodged legal claim and received financial compensation were collected. Inter-group comparisons of the prevalence of poor physical and mental health, sleep and quality of life were carried according to type of fraud and the 2011-2012 National Health Survey. Results: In this conventional sample, victims of financial fraud had poorer health, more mental health and sleeping problems, and poorer quality of life than comparable populations of a similar age. Those who had received financial compensation for preferred share losses had better health and quality of life than those who had not been compensated and those who had taken out foreign currency mortgages. Conclusion: The results suggest that financial fraud is detrimental to health. Further research should examine the mechanisms through which financial fraud impacts health. If our results are confirmed psychological and medical care should be provided, in addition to financial compensation.